Responsible Procurement Leading the Way to a Sustainable Tomorrow - Aichbauer, Stefan; Buchhauser, Martina; Erben, Agnes; Steinert, Sven; Tietze, Detlef; Wiking, Emilia (Management for Professionals,, 2022)
This open access book emphasizes that procuring goods at the expense of the environment and those who live there is no longer acceptable. Fortunately, there is now an unstoppable force, created by a collective of diverse stakeholders, driving the sustainability agenda. A company's sustainability standards can only truly be as good as those along its entire supply chain. The purpose of this book is to encourage and inspire companies on their journey to transform into responsible and sustainable businesses by addressing the supply chain, which reflects a significant part of a company's expenses and thus the impact procurement can make. The authors, accomplished procurement leaders, and experienced management consultants offer an end-to-end sustainability approach, from defining targets and ambitions to anchoring sustainability within an organization and its decision-making processes.